The Influence of Different Implant Placement Techniques on Alveolar Ridge Preservation: A Systematic Review and Meta-analysis - Thang, Nguyen Phu; Ly, Nguyen Thi Khanh; Toan, Do Thi Thanh; Tra, Nguyen Thu; Duc, Nguyen Minh (European Journal of Dentistry, 2025)
This systematic review and meta-analysis compares the effectiveness of three implant placement techniques: socket shield technique (SST), conventional immediate implant placement (CIIP), and delayed implant placement (DIP) in alveolar ridge preservation, implant survival rates, and esthetics. A comprehensive search was conducted in PubMed, Scopus, and the Cochrane Library, covering studies from 2012 to 2022. Inclusion criteria targeted clinical studies with a minimum follow-up of 6 months. Risk of bias was assessed using RoB-2 and ROBINS-I tools, and meta-analyses were performed using random-effects models. Sixteen studies met the inclusion criteria. SST demonstrated significantly better preservation of buccal bone thickness (standardized mean difference [SMD] = 2.94, 95% confidence interval [CI]: 1.46–4.42, p < 0.001) and height (SMD = 4.47, 95% CI: 1.96–6.98, p < 0.001) compared with CIIP. SST also resulted in higher pink esthetic scores (SMD = 1.00, 95% CI: 0.36–1.64, p = 0.002). No significant differences were found between CIIP and DIP for marginal bone loss (SMD = 0.15, 95% CI: −0.26 to 0.55, p = 0.471). However, DIP showed a lower implant failure rate than CIIP (odds ratio = 3.49, 95% CI: 1.26–9.66, p = 0.016). SST offers significant benefits in preserving alveolar bone and improving esthetic outcomes, while DIP appears to reduce implant failure risk. Further standardized studies are needed to confirm these findings and refine clinical guidelines.
Keywords: alveolar bone; socket shield; immediate implant placement